Simple Zn(ii) complexes for the production and degradation of polyesters. Issue 3 (7th January 2022) - Stewart, Jack; Fuchs, Martin; Payne, Jack; Driscoll, Oliver; Kociok-Köhn, Gabrielle; Ward, Benjamin D.; Herres-Pawlis, Sonja; Jones, Matthew D.
Abstract : Nine new complexes based on thioether appended iminophenolate (ONS) ligands have been prepared and fully characterized in solution by NMR spectroscopy. Abstract : Nine new complexes based on thioether appended iminophenolate (ONS) ligands have been prepared and fully characterized in solution by NMR spectroscopy. Solid-state structures were also obtained for seven complexes. In solution, all complexes were monomeric. The complexes were highly active for the polymerization of purified rac -lactide ([M] : [Zn] : [BnOH] = 10 000 : 1 : 30 at 180 °C) reaching TOF values up to 250 000 h −1 . The kinetics of the polymerization have been probed by in situ Raman spectroscopy. The rate of reaction was dramatically reduced using technical grade rac -lactide with increased initiator loading. To move towards a circular economy, it is vital that catalysts are developed to facilitate chemical recycling of commodity and emerging polymeric materials. In this vein, the complexes have been assessed for their ability to break down poly(lactic acid) and poly(ethylene terephthalate). The results from both the polymerization and degradation reactions are discussed in terms of ligand functionality.